Hyperelastic characterization oriented to finite element applications using genetic algorithms. (July 2019) - López-Campos, José A.; Segade, Abraham; Casarejos, Enrique; Fernández, José R.; Días, Gustavo R.
Highlights: A genetic algorithm is developed for the characterization of hyperlastic materials. Comparison with two commercial packages is provided. The results obtained with two well-known approximations are included into a FE solver. Abstract: In this work we highlight the capabilities of genetic algorithms to characterize the behavior shown by hyperelastic materials. We use three fitting tools, two of them included in commercial Finite Element packages and one developed using genetic algorithm methods. Four classic hyperelastic models are employed to test the different tools and to characterize a rubbery material. We show that automatic tools provide accurate data in limited ranges depending in the models. Indeed, not always can fit large strain ranges for the models. However, the dedicated genetic algorithm method performed correctly with all models and wide strain ranges, providing a robust and efficient fitting method. The results are included in a finite element model to study the differences appearing for complex stress states produced only by the selection of the material model. Compressibility effects are also studied to show the large differences in the results if only uniaxial tensile test data is used to characterize compressible hyper-elastic materials, independently of the efficiency of the fitting tools and the selection of the material model.